Carbapenem-resistant Klebsiella pneumoniae sepsis in corticosteroid receipt mice: tigecycline or colistin monotherapy versus tigecycline/colistin combination. (October 2014) - Demiraslan, Hayati; Dinc, Gokcen; Ahmed, Salman Shaheer; Elmali, Ferhan; Metan, Gokhan; Alp, Emine; Doganay, Mehmet
Abstract : This study compared the effect of monotherapy of colistin, tigecycline, and their combination in sepsis model of mice. OXA-48 producing Carbapenem-resistant Klebsiella pneumoniae (CRKP) strain was used in Balb/c mice. The mice were divided into competent and Methylprednisolone acetate (MPA)-treated groups. Each group was sub-divided into (1) colistin or (2) tigecycline monotherapy and (3) colistin/tigecycline combination therapy. After 3 hours of intraperitoneal bacterial inoculation, antimicrobials were administered, and mice were sacrificed at 24 and 48 hours Time-kill curve study demonstrated that colistin sulphate had early bactericidal activity following re-growth. In competent and MPA-treated groups of mice at 24 hours, bacterial counts in liver samples significantly lowered compared to control, however, there were no statistically differences between monotherapy and combination therapy subgroup. Bacterial count in lung samples of competent group was significantly lesser than control for all three antimicrobial subgroups at 24 hours Colistin plus tigecycline combination therapy was not superior against colistin or tigecycline monotherapy.